2009
DOI: 10.1254/jphs.08325sc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Prostaglandin E1 Analog Limaprost on Mechanical Allodynia Caused by Chemotherapeutic Agents in Mice

Abstract: Abstract. This study examined in mice whether limaprost, a prostaglandin E 1 analog, would relieve allodynia induced by chemotherapeutic agents. Single intraperitoneal injections of paclitaxel, oxaliplatin, and vincristine sulfate induced and gradually increased mechanical allodynia. Repeated administration of limaprost alfadex inhibited the late, but not early, phase of mechanical allodynia induced by paclitaxel and oxaliplatin, but not vincristine. Paclitaxel and oxaliplatin, but not vincristine, gradually d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 16 publications
(16 reference statements)
8
48
0
Order By: Relevance
“…55 Finally, concerning the opioid system, administration of a complete inhibitor of enkephalincatabolizing enzymes (PL37) also induced an antinociceptive and anti-allodynic effect, but were not effective on cold allodynia. 57 More recently, to investigate if blood flow reduction is involved in this neuropathy, Gauchan et al 58 assessed the effect of limaprost, a prostaglandin E1 analog, on mechanical allodynia without effectiveness.…”
Section: Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Finally, concerning the opioid system, administration of a complete inhibitor of enkephalincatabolizing enzymes (PL37) also induced an antinociceptive and anti-allodynic effect, but were not effective on cold allodynia. 57 More recently, to investigate if blood flow reduction is involved in this neuropathy, Gauchan et al 58 assessed the effect of limaprost, a prostaglandin E1 analog, on mechanical allodynia without effectiveness.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…26,63 Repeated administration of limaprost, contrary to vincristine, significantly inhibited the late phase of mechanical allodynia induced by a single injection of paclitaxel. 58 Therefore, repeated administration of acetyl-L-carnitine (ALC) displayed a significant attenuation of established paclitaxel-induced mechanical hypersensitivity, but this analgesic effect dissipated shortly after ALC discontinuation.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…The recommended dose of paclitaxel is 210 mg/m 2 body surface area (package insert of Taxol Âź ; Bristol-Myers Squibb, New York City, NY, U.S.A.), which corresponds to 5.9 mg/kg when the height and body weight are 170 cm and 60 kg, respectively. 11) In in vitro experiments, paclitaxel was dissolved in 100% dimethyl sulfoxide (DMSO), which was diluted in the medium so that the final concentration of DMSO was 1%. Aucubin (Wako Pure Chemical Industries, Ltd., Osaka, Japan: Lot.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, paclitaxel-and vincristine-evoked neuropathic pain is reduced by both the T-type channel calcium blocker, ethosuximide, and the 2 calcium channel subunit antagonist, gabapentin [30,31]. In addition, paclitaxel has been reported to increase the expression level of 2 -1 mRNA in the dorsal spinal cord [30,32]. Accordingly, it has been proposed that 2 -1 subunit in the spinal dorsal horn and DRG is a main site where gabapentin inhibits paclitaxel-induced allodynia [33].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated a correlation between the increase in interleukin 6 (IL-6) and the appearance of bortezomibinduced neuropathic pain [44]. Further, the administration of the prostaglandin E 1 (PGE 1 ) analog, limaprost, attenuated mechanical allodynia induced by paclitaxel and oxaliplatin (but not by vincristine) [32]. An increase in skin Langerhans cells (LC) has been associated with the development of pain in vincristine-and paclitaxel-evoked neuropathy [21].…”
Section: Introductionmentioning
confidence: 99%